Podmioty moralności. Studium porównawcze opowieści o mordercach („African Psycho’ Alaina Mabanckou i „American Psycho” Breta Eastona Ellisa) - Poręba, Izabela (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The article is a comparative study of two stories about murderers, characters of the novels “African Psycho” (2003) by Alain Mabanckou and “American Psycho” (1991) by Bret Easton Ellis. The similarities in the construction of the main characters – fascination with popular culture, brutality and vulgarity, identity problems and interest in famous serial killers – are evidence of Mabanckou’s intertextual play with a popular American novel. The essence of this play, however, is rather the moments of distinguishing and negotiating with the original text, among them: cultural, social, economic and political differences in the construction of the world presented, different class positions and motivations for the actions of the murderers. The article investigates also the main characters’ capability to be subjects of moral judgements. Their specific mental state (biographical discontinuity, isolation, desire for evil) is evidence of „depowerment”. Therefore, their capacity for self-understanding and ethical responsibility is questioned.
Moral Subjects. Comparative Study of Stories about Murderers (“African Psycho” by Alain Mabanckou and “American Psycho” by Bret Easton Ellis)
Keywords: postcolonialism; evil; murder; African Psycho; American Psycho; morality; “mental colonisation”; postkolonializm; zło; morderstwo; moralność; „kolonizacja mentalna”